How to Calculate the Public Psychological Pressure in the Social Networks - Rui Jin; Hong-Li Zhang; Xing Wang; Xiao-Meng Wang (Universitas Ahmad Dahlan, 2017)
With the worldwide application of social networks, new mathematical approaches have been developed that quantitatively address this online trend, including the concept of social computing. The analysis of data generated by social networks has become a new field of research; social conflicts on social networks occur frequently on the internet, and data regarding social behavior on social networks must be analyzed objectively. This type of social computing method can solve a series of complex social computing problems including the calculation of public psychological pressure. The quantitative calculation of public psychological pressure is so important to the public opinion analysis that it can be widely applied in a lot of public information analysis fields.